The Applicability of the Results in the Asian Population of ORIENT-11 to a Western Population According to the ICH-E5 Framework - Liu, Stephen V.; Nagasaka, Misako; Stefaniak, Victoria; Gruver, Kristi; Lin, Yong; Ferry, David; Socinski, Mark A.; Zhang, Li (Frontiers in Oncology, 2022)
Sintilimab combined with pemetrexed and platinum met the primary end point of improving progression-free survival (PFS) as first-line therapy for nonsquamous non-small-cell lung cancer (NSCLC) in the Phase 3 trial ORIENT-11 (NCT03607539). As seen in similar trials, the addition of sintilimab, a PD-1 inhibitor, to chemotherapy improved PFS without significantly worsening toxicity, with improvements in response rate and duration of response. In contrast to previous trials, the ORIENT-11 trial was conducted completely in China. Both intrinsic and extrinsic factors are important to consider when reviewing foreign clinical trial data, as they may influence efficacy and safety outcomes. Here we discuss the applicability of ORIENT-11 clinical results to a Western population.